2011
DOI: 10.1007/s00468-011-0544-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and chemical leaf composition of Mediterranean evergreen tree species according to leaf age

Abstract: Changes in morphology [leaf dry mass per unit area (LMA), thickness and density] and chemical composition (macronutrients and fibres content) in different age leaves of eight evergreen Mediterranean woody species were investigated. LMA and leaf thickness increased with leaf age increasing. Young tissues possessed higher concentrations of N, P, K, and Mg and lower Ca concentrations on a dry mass basis. However, mineral content was independent of age on leaf area basis (except for Ca content) suggesting that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
4
16
0
1
Order By: Relevance
“…The significantly thicker leaves found for four year-old seedlings of both species from our study, matches with the increasing in thickness and leaf mass dry per unit area between cohorts reported for seedlings of the same species (Mediavilla et al 2011). Furthermore, species with a long average leaf life span, Q. ilex in this case (Mediavilla & Escudero 2003), tend to have high leaf thickness and mass per unit area, low nutrient concentrations and show maximum photosynthetic rates (Poorter et al 2009).…”
Section: Leaf Morphological Variation In Q Ilex Q Suber Seedlingssupporting
confidence: 87%
“…The significantly thicker leaves found for four year-old seedlings of both species from our study, matches with the increasing in thickness and leaf mass dry per unit area between cohorts reported for seedlings of the same species (Mediavilla et al 2011). Furthermore, species with a long average leaf life span, Q. ilex in this case (Mediavilla & Escudero 2003), tend to have high leaf thickness and mass per unit area, low nutrient concentrations and show maximum photosynthetic rates (Poorter et al 2009).…”
Section: Leaf Morphological Variation In Q Ilex Q Suber Seedlingssupporting
confidence: 87%
“…Photosynthetic pigments (mainly chlorophylls a and b) in new foliage increase from the spring to the late growth season (Demarez et al, 1999;Gond, De Pury, Veroustraete, & Ceulemans, 1999;Zhang, Chen, Miller, & Noland, 2008), resulting changes of absorption features in the visible region. Leaf morphology, including LMA, leaf thickness, and leaf density, changes with leaf development (Mediavilla, González-Zurdo, García-Ciudad, & Escudero, 2011). We found seasonal changes in new pine needle morphology including needle thickness, length, width and density (unpublished data).…”
Section: Discussionmentioning
confidence: 62%
“…We propose that hyperspectral leaf reflectance can provide an efficient and accurate tool with which to monitor leaf age and intraspecific variation in leaf traits, and thereby enhance our understanding of the mechanisms underlying remotely detected patterns. Our proposed methodology takes advantage of the fact that many leaf-scale biochemical and anatomical traits that change with leaf age, for example leaf pigmentation, nutrient content, intercellular structure, leaf mass per unit area (LMA) and leaf water content (LWC) (Field & Mooney, 1983;Carter et al, 1989;Miller et al, 1991;Reich et al, 1991;Kitajima et al, 1997Kitajima et al, , 2002Escudero & Mediavilla, 2003;Mediavilla et al, 2011), have been shown to directly influence the spectral reflectance behaviour of leaves (Gausman et al, 1970;Knipling, 1970;Roberts et al, 1998;Datt, 1999;Sims & Gamon, 2003). A few studies have also observed significant intra-specific variability in leaf spectral reflectance of trees as a result of differences in leaf age (Roberts et al, 1998;Datt, 1999;Lewis, 2002).…”
Section: Introductionmentioning
confidence: 99%